Binocular vision anomalies and normative data (BAND) in Tamil Nadu: report 1. (30th October 2016) - Hussaindeen, Jameel Rizwana; Rakshit, Archayeeta; Singh, Neeraj Kumar; Swaminathan, Meenakshi; George, Ronnie; Kapur, Suman; Scheiman, Mitchell; Ramani, Krishna Kumar
Abstract : Background: This population‐based, cross‐sectional study was designed to determine normative data for binocular vision and accommodative testing in rural and urban populations of Tamil Nadu. Methods: A sample of 936 was determined, based on a previous pilot study. The epidemiological field work included a comprehensive eye examination and a binocular vision and accommodative assessment carried out in a total of four public schools, two each in the rural and urban arms of Chennai. An overall sample of 3, 024 children between seven and 17 years of age was screened in the four schools and 920 children were included in the study. Results: We found significant differences in expected values from the current clinical criteria for near point of convergence (NPC) with penlight, distance and near horizontal phorias, vergence facility, accommodation convergence/accommodation (AC/A) ratio, accommodative amplitudes, monocular and binocular accommodative facility (t‐test: p < 0.001). The mean and standard deviation break/recovery values for NPC (in centimetres) with an accommodative target and penlight with red filter was 3 ± 3/4 ± 4 and 7 ± 5/10 ± 7, respectively. The mean accommodative amplitudes for the population could be estimated from the linear regression equation 16 – 0.3 × (age). The vergence facility was 12 ± 4 cycles/minute and 14 ± 4 cycles/minute in the seven to 10 and 11 to 17 age groups, respectively. Monocular accommodative facility was 11 ± 4 cycles/minute and 14 ± 5 cycles/minute and binocular accommodative facility was 10 ± 4 cycles/minute and 14 ± 5 cycles/minute in the seven to 12 and 13 to 17 age groups, respectively. The mean calculated AC/A ratio was 5.4 ± 0.6/1. Conclusion: The normative data for vergence and accommodative parameters for the Indian children between seven and 17 years of age are reported. The developmental trend of accommodation and vergence differences and significant differences in cut‐off between the current data and available literature are reported. These differences have clinical implications for the interpretation, diagnosis and management of anomalies of binocular vision.